Harnessing Renewable Energy for Sustainable Agricultural Applications - Babatunde, Olubayo M.; Denwigwe, Iheanacho H.; Adedoja, Oluwaseye S.; Babatunde, Damilola E.; Gbadamosi, Saheed L. (International Journal of Energy Economics and Policy, 2019)
The 2030 Agenda for Sustainable Development suggests that all countries both developed and developing strive to attain the seventeen sustainable development goals (SDGs). Some items on the SDGs like implementation of renewable energy technologies to electrify regions disconnected from power grids are targeted to eradicate extreme poverty and hunger while ensuring environmental sustainability. Hence, the role of integrated renewable energy in improving the productivity and environmental sustainability of the agricultural sector cannot be overemphasized. This paper presents a brief survey of the application of renewable energy resources technologies in the agricultural sector. Keywords: Sustainable agriculture; Water-food-energy nexus; Renewable energy; Techno-economic. JEL Classifications: Q2, Q4 DOI: https://doi.org/10.32479/ijeep.7775